A preliminary study on new cooling techniques for stingless bees hive - Luqman, Abdul Halim; Firdaus, Basrawi; Mohd Yusof, Taib; Mohd Hazwan, Yusof; Zulkifli, Mustafa; Thamir K., Ibrahim (IOP Publishing, 2020)
Stingless bees are a type of insect which are very sensitive to the changes of their surroundings, especially to severe heat wave. A report stated that at temperature as high as 38 ºC can cause death of the bees especially to the pupae. Therefore, the objective of this research is to evaluate new methods in regulating the temperature in the hive. To achieve this goal, two cooling methods were studied. One method is using greenroof, a type of roof which contains green vegetation and soil. It is used to cool down the space under the roof. Another method is using a photovoltaic (PV) powered thermoelectric cooler (TEC). Three units of MUSTAFA-hives were exposed under sunlight, one is without any temperature regulation and the other two hives used cooling techniques stated above. The temperatures inside each hive was measured at two points, and was compared with the hive without temperature regulation. It was found that, for the hive integrated with greenroof, the average hive temperature was about 3 ºC and 6 ºC lower in the honey cassette and brood-cells compartment, respectively. On the other hand, the hive with PV powered TEC recorded average temperatures of about 0.5 °C and 3 °C lower in honey cassette and brood-cells compartment, respectively. Therefore, it can be concluded that the implementation of greenroof or TEC could solve the problem of stingless bees’ hive overheating. However, the greenroof has a better thermal performance, besides being economic and simpler solution.